Factors associated with pathologic complete response following neoadjuvant chemoradiation and esophagectomy for carcinoma of esophagus and gastroesophageal junction. Issue 1 (21st September 2022) - Nusrath, Syed; Thammineedi, Subramanyeshwar R.; Raju, Kalidindi Venkata Vijaya Narsimha; Patnaik, Sujith C.; Saksena, Ajesh R.; Karthik, Jaya; Basude, Madhunarayana; Kumar J, Pavan; Shukla, Srijan; Rao, Vishal B.; Kumar C, Kishore; Gujjuru, Swathi; et al.
Abstract: Background and Objectives: The aim of this study was to analyze factors associated with pathologic complete response (pCR) following neoadjuvant chemoradiation (NCRT) and esophagectomy for carcinoma of the esophagus (EC) and gastroesophageal junction (GEJ). Methods: Patients with EC and GEJ tumors who received NCRT and underwent esophagectomy between January 2010 to March 2021 were included. Univariate and multivariate analyses were performed to evaluate the factors associated with pCR by comparing the patients who achieved pCR (pCR group) with those who did not achieve pCR (non‐pCR group). Results: A total of 321 patients were included in the study, with squamous cell carcinoma (SCC) accounting for the majority of cases (76%). One hundred and sixty (49.8%) patients had pCR. SCC histology and pretreatment radiographic node‐negative status (cN0) were associated with pCR. Patients in the pCR group had significantly better overall and disease‐free survival compared with patients in the non‐pCR group. Conclusions: SCC histology and pretreatment radiographic node‐negative status were associated with pCR. For patients with tumors of EC and GEJ who received NCRT and underwent esophagectomy, pCR was associated with improved prognosis compared with those not achieving pCR.